Arctic observers: Richard King, monogenism and the historicisation of Inuit through travel narratives. (June 2015) - Sera-Shriar, Efram
Abstract: In 1848 the ethnologist, surgeon and Arctic explorer Richard King (1810–1876) published a three-part series on Inuit in the Journal of the Ethnological Society of London. This series provided a detailed history of Inuit from the eleventh century to the early nineteenth century. It incorporated a mixture of King's personal observations from his experience travelling to the Arctic as a member of George Back's expedition (1833–1835), and the testimonies of other contemporary and historical actors who had written on the subject. The aim was to historicise Inuit through the use of travel reports and show persistent features among the race. King was a monogenist and his sensitive recasting of Inuit was influenced by his participation in a research community actively engaged in humanitarian and abolitionist causes. The physician and ethnologist Thomas Hodgkin (1798–1866) argued that King's research on Inuit was one of the best ethnological approaches to emulate and that it set the standard for the nascent discipline. If we are to take seriously Hodgkin's claim, we should look at how King constructed his depiction of Inuit. There is much to be gained by investigating the practices of nineteenth-century ethnologists because it strengthens our knowledge of the discipline's past and shows how modern understandings of races were formed.